Contesting race and citizenship : youth politics in the black Mediterranean - Hawthorne, Camilla A. (Cornell University Press, 2022)
"Drawing on ethnographic and archival research, this book explores the political mobilizations of Black Italians, the children of African and Afro-Latinx immigrants who were born and raised in Italy, as they engage with questions of citizenship, state racism, and global Black diasporic interconnection"--